Cooperative Relationship between Teachers and Parents: Develop Learning Ability for Primary School Students during the Covid-19 Pandemic - Wibowo, Dodiet Enggar; Mahmudi, Ali; Retnawati, Heri (LPPM Undiksha, 2021)
Educators and students have suffered greatly from the Covid-19 pandemic. As a result of the Covid-19 pandemic, almost all of schools had to deactivate its activities. During the Covid-19 pandemic, the role of parents is very much needed in helping the learning process at home. This study aims to develop the learning abilities of elementary school students during the Covid-19 pandemic by establishing cooperative relationships between teachers and parents. Respondents of this study were 11 teachers and 8 parents. Confidential information from respondents, all answers and the identity given are kept confidential. The research design are exploratory case studies, data collection instruments with semi-structured interview methods, and Focused group Discussion (FGD). The data analysis in this study consisted of studying, categorizing, tabulating, combining empirical evidence to build initial propositions. The process of data collection and data analysis are carried out simultaneously which then continued after data collection is complete using intensive analysis methods and interactive models. The results of the research on the impact of Covid-19 showed that online learning are not effective compared to face-to-face learning in the classroom, the obstacles in online learning including unstable networks, and lack of parents’ ability to help explaining the material provided by the teacher. Good cooperation and communication between parents and teachers are the solution to optimize study from home.